Ingress and Egress to Utility Trucks – Design of Steps and Stairs. (September 2014) - Saginus, Kyle; Marklin, Richard; Seeley, Patricia; Stone, Amy
The design of the structures that workers use to enter and exit utility trucks can affect the safety of workers. Workers can access the truck via the cab or via the truck bed on the side or rear. Large vehicles, such as aerial trucks in a utility fleet, can increase the risk of a slip or fall because of its taller height above the ground. The authors conducted a study for EPRI (Electric Power Research Institute) that included meas-urements of the steps and stairs of 29 electric fleet vehicles and a review of the standards related to struc-tures for ingress and egress. The authors present design configurations of steps, stairs, and pullout ladders for access to utility trucks from the cab, side, and rear. These examples include specific dimensions of the riser height and tread width, depth of stairs, and stair inclination angle. Design of access to the bucket of an aerial truck is not included. Ergonomists and vehicle designers can use the comparison table of standards along with the design examples to help them design ingress and egress structures for trucks that may reduce the risk of a slip or fall.